2005
DOI: 10.1074/jbc.m404851200
|View full text |Cite
|
Sign up to set email alerts
|

Cellugyrin Induces Biogenesis of Synaptic-like Microvesicles in PC12 Cells

Abstract: The four-transmembrane domain proteins synaptophysin and synaptogyrin represent the major constituents of synaptic vesicles. Our previous studies in PC12 cells demonstrated that synaptogyrin or its nonneuronal paralog cellugyrin targets efficiently to synapticlike microvesicles (SLMVs) and dramatically increases the synaptophysin content of SLMVs (Belfort, G. M., and Kandror, K. V. (2003) J. Biol. Chem. 278, 47971-47978). Here, we explored the mechanism of these phenomena and found that ectopic expression of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
(30 reference statements)
0
20
0
Order By: Relevance
“…Extracts of transfected adipocytes were incubated with an excess of the anti-Myc antibody (or non-specific IgG) together with nanogold-conjugated goat anti-mouse Fab fragments. During the incubation period, the heavy antibody–Fab–nanogold complex bound to the cytoplasmic Myc epitope of the target proteins, and ‘decorated’ and ‘non-decorated’ vesicles were then analysed by sucrose-gradient centrifugation (see also [23]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracts of transfected adipocytes were incubated with an excess of the anti-Myc antibody (or non-specific IgG) together with nanogold-conjugated goat anti-mouse Fab fragments. During the incubation period, the heavy antibody–Fab–nanogold complex bound to the cytoplasmic Myc epitope of the target proteins, and ‘decorated’ and ‘non-decorated’ vesicles were then analysed by sucrose-gradient centrifugation (see also [23]).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike IRVs that compartmentalize most of the intracellular GLUT4, cellugyrin-containing vesicles are completely resistant to insulin stimulation and cellugyrin is not translocated to the plasma membrane in response to insulin ([21,22] and the present study). Last, but not least, the C-terminus of cellugyrin does not carry any targeting information [23], which is essential for the interpretation of results. We have found that the C-terminus of GLUT4 is required for protein localization in the perinuclear compartment, but is not sufficient for the efficient targeting to the IRVs.…”
Section: Introductionmentioning
confidence: 99%
“…Synaptophysin binds cholesterol and promotes the formation of highly curved membranes (Thiele et al, 2000). Overexpression of cellugyrin, a non-neuronal paralog of synaptogyrin, induces the formation of synaptic-like microvesicles (SLMVs) in neuroendocrine cells (Belfort et al, 2005). Synaptophysin may also participate in synaptic vesicle recycling through a Ca 2+ -dependent interaction with dynamin, as the inhibition of this interaction results in a smaller synaptic vesicle pool following high-frequency stimulation (Daly et al, 2000; Daly and Ziff, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This notion is supported by the multiple interactions of TVPs with lipids, notably cholesterol (8) or various components of the recycling machinery including soluble N-ethylmaleimide-sensitive fusion attachment protein receptors (SNAREs) (9-11), dynamin (12, 13), adaptor proteins (14), and eps15 homology (EH)-domain proteins (15). In addition, it has been postulated that TVPs are directly responsible for microvesicle formation (8,16,17) and are involved in fusion pore formation (18-21).…”
mentioning
confidence: 99%